2023
DOI: 10.3390/su15031961
|View full text |Cite
|
Sign up to set email alerts
|

Green Innovation, Self-Efficacy, Entrepreneurial Orientation and Economic Performance: Interactions among Saudi Small Enterprises

Abstract: The stiff competition in the market, and continuous pressures from various stakeholders such as customers, business owners, environmental authorities, and society, in general, to produce unique products and services, protect the environment, and obtain competitive advantage continue to challenge the sustainability of enterprises in the market, especially the small ones. Accordingly, to minimize the effect of these challenges and pressures, small enterprises can improve their performance by directing their prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 101 publications
0
21
0
Order By: Relevance
“…Interestingly, we found that GEO’s effect on GPROCI is higher than on GPRODI. These results reflect the importance of GEO for promoting sustainability, for example, in thinking, creation, innovations, motivations and operations, which bring superior competitive advantages in emerging economies (Alshebami, 2023; Asadi et al , 2020; Guo et al , 2020; Majali et al , 2022; Jiang et al , 2018), and developed economies (Skordoulis et al , 2022).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Interestingly, we found that GEO’s effect on GPROCI is higher than on GPRODI. These results reflect the importance of GEO for promoting sustainability, for example, in thinking, creation, innovations, motivations and operations, which bring superior competitive advantages in emerging economies (Alshebami, 2023; Asadi et al , 2020; Guo et al , 2020; Majali et al , 2022; Jiang et al , 2018), and developed economies (Skordoulis et al , 2022).…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, while some studies have empirically explored the GEO–GI link (e.g. Alshebami, 2023; Muangmee et al , 2021), their attention has mostly been on the direct effect of GEO on GI, without delving into the conditions under which GEO affects GI, particularly GPRODI and GPROCI. On the other hand, our study extends the work of Guo et al (2020), who investigated the mechanisms through which GI can be fostered in green entrepreneurship-oriented firms by revealing that ROC moderates the GEO–GPRODI link.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most literature emphasizes that enterprises with high relational abilities could have superior advantages. Mainly, the literature shows that a specific competitive advantage is developed via connections with business associates and could only be obtained and continued if enterprises establish vibrant abilities to sustain such network relations concerning environmental changes (Alshebami, 2023; Novitasari et al, 2021; Rodríguez‐Díaz & Espino‐Rodríguez, 2006; Wei et al, 2023; Yin & Shi, 2019). In relationship disbanding, relational embeddedness is hard to redevelop and lose.…”
Section: Introductionmentioning
confidence: 99%